The Palestinian Elite’s Use on Digital Diplomacy in the Face of the Israeli Narrative - Abu Naqira, Ayman Khamis Rabee; Abu Hashish, Yousef Yahya Ali (ALBAHITH ALALAMI, 2023)
This study aims to determine the extent to which Palestinian elites use digital diplomacy to confront the Israeli narrative by exploring the motives for usage, patterns, essential digital diplomatic tools, and achieved satisfactions. The study adopted a survey methodology and employed a questionnaire distributed to a sample of 110 Palestinian political and media elites. The study arrived at several key findings, including: Palestinian elites allocate a substantial (%67) of their efforts towards employing digital diplomacy as a response to the Israeli narrative. The foremost platforms employed for this purpose are Facebook and Twitter. The primary motivation for utilizing these digital platforms is to present the Palestinian perspective to a global audience, while the central objective is to debunk the false Israeli narrative, which relies heavily on targeted propaganda.